ROH KUDUS DALAM TRINITAS DAN KOMUNITAS UMAT TUHAN (HOLY SPIRIT IN THE TRINITY AND COMMUNITY OF GOD'S PEOPLE) - Steven Tubagus; Timotius Bakti Sarono (QUAERENS: Journal of Theology and Christianity Studies, 2021)
The doctrine of the Holy Spirit and its praxis has been controversial among God's people. This controversy has even emerged since the beginning of the church about the person and position of the Holy Spirit with God the Father and the Son. This article aims to briefly explore the doctrine of the Holy Spirit and its praxis into the community of God's people. The writing method used is a praxis systematic critical method to examine the various nuances of the argument against the Holy Spirit with the aim of placing it in a proper understanding of the trinity concept. The result of this writing is the doctrine of the Holy Spirit there is no personality difference between God the Father, the Son and the Holy Spirit, because humans meet these "persons" in every spiritual aspect. By conceptualizing God in the realm of the Spirit of God, it will be a more practical way to describe activities in community life. Doktrin Roh Kudus dan praksisnya telah memberikan kontroversi selama ini di antara umat Tuhan. Kontroversi ini bahkan sudah muncul mulai permulaan gereja bagaimana pribadi dan posisi Roh Kudus dengan Allah Bapa dan Putra. Artikel ini bertujuan mengeksplorasi secara singkat doktrin Roh Kudus dan praksisnya ke dalam komunitas umat Tuhan. Metode penulisan yang digunakan adalah metode kritis sistematis praksis untuk menelaah berbagai nuansa argumen terhadap Roh Kudus dengan tujuan menempatkannya dalam pemahaman yang tepat tentang konsep trinitas. Hasil dari penulisan ini adalah doktrin Roh Kudus tidak ada perbedaan kepribadian antara Allah Bapa, Anak dan Roh Kudus, karena manusia bertemu dengan “pribadi-pribadi” ini dalam setiap aspek rohani. Dengan mengkonseptualisasikan Tuhan dalam alam Roh Allah akan menjadi cara yang lebih praktis untuk menggambarkan aktivitas secara kehidupan komunitas.